Pragmatic Analysis of Maxim Non-Observance in Medical Crisis Communication Raditya Dika Podcast - Diyan Adeyanti; Rega Kurniawan; Cecep Agus (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores how conversational meaning is created through the deliberate non-observance of Grice’s Cooperative Principle in a humor-based Indonesian podcast. The purpose of this research is to understand not only how speakers flout conversational maxims, but also why they do so and how these choices help convey humor, engage listeners, and make complex information easier to understand. The study uses a qualitative descriptive method with a pragmatic approach, drawing data from an episode of the Raditya Dika Podcast titled Cerita dari Ruang IGD, featuring Dr. Gia Pratama, which discusses a real medical emergency case. The analysis identifies instances where speakers intentionally break the maxims of Quantity, Quality, Relation, and Manner to create meaning beyond the literal words. The findings reveal 15 instances of maxim flouting, with Quality occurring most often, followed by Manner, Quantity, and Relation. These strategies are used to dramatize events, express professional awe, manage emotional tension, and translate complicated medical experiences into stories that are engaging and accessible. Overall, the study shows that deliberately flouting conversational maxims allows speakers to balance humor with sensitive content, making the podcast both informative and entertaining. This highlights the role of pragmatic choices in digital discourse and suggests that humor can be an effective tool for presenting serious topics in ways that are clear, relatable, and engaging for listeners.